2022
DOI: 10.1038/s41598-022-12959-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of body mass reduction on functional stability in young obese women

Abstract: Functional stability is necessary for everyday activities. The studies have indicated the deterioration of functional stability during standing in the obese adults. This study aimed to determine whether the 3-month weight-loss program that resulted in body mass reduction equal to or greater than 5% of the initial body mass would improve functional stability in young obese women. For the purpose of this study, the data of 30 females were included. Their mean age was 35.8 ± 9.2. The women performed the anterior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(41 reference statements)
1
1
0
Order By: Relevance
“…However, the present study did not find a correlation between BMI and postural dynamic balance, even though 88.7% of the sample were morbidly obese. It can be inferred that these findings are related to those found by Cieślińska-Świder et al 19 who suggested that people with obesity increases balance using a compensatory mechanism of widening the base of support.…”
Section: Discussionsupporting
confidence: 81%
“…However, the present study did not find a correlation between BMI and postural dynamic balance, even though 88.7% of the sample were morbidly obese. It can be inferred that these findings are related to those found by Cieślińska-Świder et al 19 who suggested that people with obesity increases balance using a compensatory mechanism of widening the base of support.…”
Section: Discussionsupporting
confidence: 81%
“…Greater muscle weakness in the lower limbs and 34% balance disorders are common in older adults, which may be exacerbated by a variety of biological and social factors, including physical disability, chronic illnesses, incontinence, inactivity, and obesity (19). Regarding the role of gender, both younger women under 50 years of age (20,21) and older women aged 65 to 75 years (22) exhibit lower stability limits, making them more susceptible to falls. However, irrespective of gender, obesity alone leads to altered postural control, associated with increased activity of plantar flexion.…”
mentioning
confidence: 99%